Soybean radiation balance in subtropical region - Fontana, Denise Cybis; Berlato, Moacir A.; Bergamaschi, Homero (Pesquisa Agropecuaria Brasileira, 1991)
In Taquari, RS, Brazil, 29°48'S, 51°59'W, 76 m altitude, and Cfa climate, according to Köppen, the components of soybean (Glycine max (L.) Merril) cv. Bragg radiation balance were dimensioned in optimal conditions of soil water availability. Sowing date was November 21, 1985, using row spacing of 0,68 m and a plant populations of 4 x 105 plants. ha-1. Evaluations were carried out at the center of a plot with 2,500 m2; weekly at 30 min intervals, from 6 a.m. to 7 p.m. the global solar radiation, reflected short wave radiation, and net radiation were measured. For each period leaf area indexes and growth stages were measured. The results show that soybean daily average albedo was 0.26 for a LAI varying from 4.7 to 7.7 (growth stages V9 to R6). It was also demonstrated that the 24 h and the diurnal net radiation over soybeans can be estimated from the global solar radiation or from the short wave net radiation.
Keywords: Glycine max; water deficit; micrometeorology; temperature; humidity